Are Brazilian adolescents eating enough fruits and vegetables? An assessment using data from the Study of Cardiovascular Risk in Adolescents - Page BRITO, Alessandra; Dutra CALDAS, Eloisa (Revista de Nutrição, 2022)
Objective To estimate the usual consumption of fruits and vegetables by Brazilian adolescents. Methods We used 24-hour dietary recall data from the Study of Cardiovascular Risk in Adolescents conducted in 2013-2014 with 71,740 adolescents between 12 and 17 years old. The usual consumption of fruits and vegetables was estimated in the Statistical Analysis Software using the model of the United States National Cancer Institute, and evaluated according to sex, age, place of residence, economic class, and nutritional status of the participants. Results The mean of usual fruit and vegetable consumption was estimated at 171g/day, mostly fruits (128g/day), mainly in the form of fruit juice (64.8%). The minimum fruit and vegetable consumption of 400g/day recommended by the World Health Organization was reached only by 2% of the adolescents. The adolescents’ socioeconomic class or nutritional status had no impact on the usual fruit and vegetable consumption, but adolescents from northern Brazil had a significantly lower consumption than those from the midwestern region. Orange was both the most consumed fruit on a daily basis (mean of 42.6g/day, 90% as juice) and the most reported fruit (by 12.7% of the adolescents), followed by apples (10g/day; 5.6%) and bananas (8.4g/day; 8.3%). Tomato was the most consumed vegetable (9.2g/day), reported by 11.5% of the adolescents. Conclusion Public health policies are necessary to encourage fruit and vegetable consumption among Brazilian adolescents, including of pure juice, essential foods to prevent chronic diseases in adulthood.